Calcium Analysis in Bones During Aging Process - Šapčanin, Aida; Sofić, Emin (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2016)
The resorption process in bone organ culture can be measured and evaluated by only measuring the calcium concentration in the medium with calcium ion-selective electrode. Reliable and consistent calcium resorption from bone using 500 ng/ml prostaglandine E2 or 250 ng/ml human parathyroid hormone (1-34) have occurred. The results, thus, indicate that calcium can be considered as an independent index of bone resorption. Our preliminary measurements by atomic absorption spectrophotometry (AAS), although statisticaly unrepresentative the sample – group being 9 babies and 9 adults, point to such conclusion. Bones were taken postmortem or post operationem. Calcium concentration measured by AAS was at range of about 260 mg Ca/ mg ash in the human baby bones (costae) and of about 430 mg Ca/mg ash in the human adult bones (femur). Calcium amount measured also in the calvaria of five-day old mice ICR strain by AAS. Values were at range of about 45 mg Ca/mg ash. AAS is a reference method for calcium determination in human bones, however for simplification it is more appropriate to use calcium ion-selective electrode.